2003
DOI: 10.1016/s0377-1237(03)80102-8
|View full text |Cite
|
Sign up to set email alerts
|

A Two Year Experience in Continuous Positive Airway Pressure Ventilation Using Nasal Prongs and Pulse Oximetry

Abstract: In a prospective study 26 of the 116 consecutive neonates suffering from respiratory distress survived on varying concentrations of humidified oxygen. Continuous positive airway pressure (CPAP) of 4-12 cm of water was applied through short nasal prongs to 90 neonates. Haemoglobin oxygen saturation (SaO2) rose in all and it was maintained steadily above 85% in 46 (51%) infants who survived. The mean duration of CPAP among the survivors was 61 hours (range 8-190 hours). Common indications of CPAP ventilation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
2
0
2
Order By: Relevance
“…Various studies have detailed the fact that rapid raise in oxygen saturation was seen in usage of bCPAP with improvement in lung function and decreases of RDS symptoms in new born. [15][16][17][18][19] as also presented in the current study results where the success rate by using bCPAP was observed up to 76.2%.…”
Section: Discussionsupporting
confidence: 67%
“…Various studies have detailed the fact that rapid raise in oxygen saturation was seen in usage of bCPAP with improvement in lung function and decreases of RDS symptoms in new born. [15][16][17][18][19] as also presented in the current study results where the success rate by using bCPAP was observed up to 76.2%.…”
Section: Discussionsupporting
confidence: 67%
“…1,2 Respiratory distress is one of the most common diseases that affect these premature infants, and they most often require respiratory support through the use of mechanical ventilation (MV). 3,4 Medical conduct from the respiratory perspective has been directed to minimize the need for prolonged MV through respiratory assistance where aggression and time are kept as low as possible in order to reduce barotrauma and oxygen toxicity. 5,6 High morbidity occurs even with the use of surfactant, especially in premature infants requiring MV for a prolonged period.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome in these babies from their study was significantly better than those in whom there was a delay (1 hour) in commencing CPAP. The usefulness of pulse oximetry as a monitoring tool for babies on CPAP was noted by Malik et al 17 who reported a rapid rise in SPO 2 to >85% and this was sustained among survivors. This pattern of response is similar to the findings in our study.…”
Section: Discussionmentioning
confidence: 92%